Lexicographic Earliest Arrival Contraflow Evacuation Problem on UPL-TTSP Network - Khadka, Shree Ram; Bhandari, Phanindra Prasad (International Journal of Operational Research/Nepal, 2020)
An evacuation plan proposes a way out for maximum utilization of an existing transportation system so that the safest tour and most efficient evacuation time of all expected evacuees could be ensured. This paper studies the auto-based earliest arrival contraflow problem modeled on network with capacitated intermediate vertices. The vertices serve as trans-shipment vertices as well as temporary shelters of given priority order. It also proposes an efficient solution procedure to the problem for the uniform path length two terminal series parallel (UPL-TTSP) network.